Comparing the Twitter posting of British gambling operators and gambling affiliates: a summative content analysis. Issue 2 (4th May 2019) - Houghton, Scott; McNeil, Andrew; Hogg, Mitchell; Moss, Mark
ABSTRACT: The current study aimed to assess the type of content posted on Twitter by British gambling operators and gambling affiliates; third-party firms who are financially incentivized to attract custom to gambling operators. Five thousand and twenty-nine tweets from 5 gambling operators and 8315 tweets from 5 gambling affiliates were collected over a 2-week period. A summative content analysis was carried out whereby each tweet was coded for its main content. Tweets were grouped together into content categories and the percentage of tweets in each content category was calculated for both operators and affiliates. The nine categories of content found were: direct advertising, betting assistance, sports content, customer engagement, humour, update of current bet status, promotional content, safer gambling and 'other'. Gambling operators had a higher proportion of posts in the sports content and humorous content categories, whilst affiliates had a higher proportion of posts within the direct advertising and betting assistance categories. These findings suggest that the affiliates were more direct in their posting style whereas operators followed a more indirect approach, reflective of a branding strategy. Future research should address how interacting with different types of gambling content on social media impacts upon gambling attitudes and behaviour.